Rehabilitasi Pelaku Tindak Pidana Narkotika Golongan 1 (Satu) Menurut Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika - Gusye Nobert Hehalatu; Margie Gladies Sopacua; Jetty Martje Patty (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Rehabilitation is a form of punishment aimed at treatment.Purposes of the Research: The purpose of this study is to determine whether the actions of the perpetrators of the Narcotics Crime in Decision Number 154/Pid.Sus/PN Amb have fulfilled the elements of the threat of punishment as stipulated in the Narcotics Law and what the judges consider in giving a rehabilitation decision against the perpetrators of narcotics abuse.Methods of the Research: The research method used is normative juridical research or literature study with the type of research that is analytical descriptive in nature which is a method that functions to describe or give an overview of the object under study through legal sources.Results of the Research: The results of the research used, it can be concluded that the judge decided to impose a sentence in the form of medical rehabilitation. Legal actions imposed on victims of narcotics abuse are reflected in SEMA No. 04 of 2010, concerning the placement of abusers, victims of abuse and narcotics addicts into rehabilitation institutions.